The Performance Determinants of Employees of Zakat Collector (Amil) Institution: Case Study of Collectors and Empowerers of National-Scale Zakat Collector Institutions in Indonesia - Mubarok, Endang Saefuddin; Soleh, Achmad; Wiwin, Wiwin; Hidayat, Rahmat; Santoso, Rukun; Krismayadi, Krismayadi; Subagja, Asep Zamzam (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of this research was to determine how competence functions as a mediator between performance, training, and motivation. This study performed a multivariate analysis with a descriptive and explanatory quantitative strategy. The research sample consisted of 80 respondents selected by employing a proportional sampling technique. Data were collected through an instrument questionnaire and analyzed using the partial least squares (PLS) approach of structural equation modeling (SEM). The results showed that: Motivation and training both have a substantial impact on performance; Motivation and training both have a substantial impact on performance; Competence has a significant role in performance as a mediator variable, competence has a considerable ability to mediate the influence of motivation and training on performance. The results of the calculation of the square value of multiple correlations (R2) of 0.274 and 0.572 respectively show the strength of the competence dependent variable and employee performance.